Clinico-epidemiological profile of chronic kidney disease patients attending a tertiary care hospital in Goa, India - Edakkunnummel, Hasil Mohammed Ali; Tiwari, Jai Prakash; Habib, Mudasir; Tyagi, Sumit; Bhatlawande, Tejaswini; Kar, Bipasa; Nambiar, Anusree (International Journal of Research in Medical Sciences, 2026)
Background: Chronic kidney disease (CKD) is a major public health problem associated with substantial morbidity and mortality. While diabetes mellitus and hypertension remain the leading causes of CKD, increasing attention is being directed toward chronic kidney disease of unknown etiology (CKDu). In Goa, particularly the southern taluka of Canacona, systematic hospital-based data on CKD are limited. Methods: This cross-sectional study was conducted at Goa Medical College between May 2023 and April 2024. Consenting adults (>18 years) with CKD, defined according to KDIGO 2024 criteria, were enrolled. Demographic, socioeconomic, clinical, biochemical, radiological, and etiological data were collected. CKDu was defined as CKD in the absence of diabetes mellitus, long-standing hypertension sufficient to explain kidney disease, or any other identifiable cause after standard evaluation. Statistical analysis was performed using SPSS version 26. Results: Among 345 patients, 243 (70.4%) were male, with a mean age of 55.0±14.3 years. Hypertension (93.6%) and diabetes mellitus (60.9%) were the most common comorbidities. Anemia was present in 84.6% of patients, and CKD–mineral and bone disorder abnormalities were frequent. Diabetic kidney disease and hypertensive nephropathy were the predominant etiologies. CKDu was identified in 27 patients (7.8%), with marked clustering in Canacona taluka (20 cases). Conclusions: CKD in Goa is predominantly driven by diabetes and hypertension. However, clustering of CKDu cases in Canacona suggests a potential hotspot warranting focused surveillance and environmental investigations.